Pengaruh Metode Numbered Head Together (NHT) Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran IPS - KHAERANI, ZUHRATUL; Ibnu Hizam (Alpatih Harapan Semesta, 2025)
This study aims to influence the NHT method on student learning achievement in Economic Social Studies class X at MAN 2 Mataram. This research is a quasi-experimental research with hypothesis testing using paired-sample t-test on SPSS programme. The results showed that there was an average increase in student learning achievement. Where obtained Thitung = 3.243 > from Ttabel = 2.021 so that H0 is rejected. Thus Ha proposed in this study is accepted, so that it can be concluded that there is an effect of the NHT method on student learning achievement in economic social studies class X at MAN 2 Mataram in the 2011/2012 academic year.